Atopic Dermatitis in Asians: A Review on Genetics, Clinical Presentation, and Therapeutic Implications (Canadian Dermatology Today, 2025)
Atopic dermatitis (AD) is a common, multifactorial, and pruritic inflammatory skin condition with a chronic relapsing course. It typically manifests in infancy or early childhood and is often associated with other atopic conditions, such as asthma and allergic rhinoconjunctivitis. As the most prevalent chronic inflammatory skin disease worldwide, AD affects individuals across a wide range of racial and ethnic backgrounds. Recent studies suggest that Central Asia has the highest pediatric prevalence of AD in 2021, with a rate of 10.5%, surpassing the 5.4% prevalence observed in high‑income North America. According to the 2021 Census, individuals of Asian descent constitute the third-largest population group in Canada, following those of European and North American descent, with nearly half originating from East or Southeast Asia. Furthermore, Asians represent Canada’s fastest-growing demographic. This review highlights the genetic factors, clinical presentations, and therapeutic considerations for AD in Asian populations, aiming to improve understanding and inform tailored treatment approaches.